2012
DOI: 10.1038/srep00332
|View full text |Cite
|
Sign up to set email alerts
|

Infection of specific strains of Streptococcus mutans, oral bacteria, confers a risk of ulcerative colitis

Abstract: Although oral bacteria-associated systemic diseases have been reported, association between Streptococcus mutans , pathogen of dental caries, and ulcerative colitis (UC) has not been reported. We investigated the effect of various S. mutans strains on dextran sodium sulfate (DSS)-induced mouse colitis. Administration of TW295, the specific strain of S. mutans , caused aggravation of colitis; the standard strain, MT8148 did not. Localization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 29 publications
1
83
0
Order By: Relevance
“…Though renal insufficiency is known to be a complication of IE, the relationship between S. mutans and kidney disease remains to be elucidated, and further studies should be performed. We previously reported that S. mutans might be a potential risk factor in aggravation of ulcerative colitis (58). In the present study, gastrointestinal hemorrhage and cystorrhagia were also observed.…”
Section: Figsupporting
confidence: 60%
“…Though renal insufficiency is known to be a complication of IE, the relationship between S. mutans and kidney disease remains to be elucidated, and further studies should be performed. We previously reported that S. mutans might be a potential risk factor in aggravation of ulcerative colitis (58). In the present study, gastrointestinal hemorrhage and cystorrhagia were also observed.…”
Section: Figsupporting
confidence: 60%
“…Avid binding of collagenous tissues is an important mechanism utilized by a subset of S. mutans strains expressing CBPs to successfully colonize oral and extraoral tissues (1,22,24,26,27,49). This study highlights two important characteristics that can be attributed to Cnm, (i) enhanced invasion of epithelial cell lines relevant to soft tissues of the oral cavity and (ii) stringent adherence to collagenous oral hard tissues, which enhance the colonization and cariogenic potentials of certain S. mutans strains.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated that streptococci dominate the intracellular flora of buccal cells in vivo (50) and have also linked Cnm expression in S. mutans with invasion of HCAEC (26) and HUVEC (27) and adherence to hepatocytes (49). These observations prompted our investigation into Cnm-mediated attachment to, and invasion of, oral epithelial cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…S. mutans has several major surface protein antigens, including collagen-binding protein (Cnm), a cell surface collagen-binding protein related to the ability to bind to the extracellular matrix, which has been purified and its encoding gene specified [15]. Our recent studies suggest that cnm -positive S. mutans strains could be associated with aggravated cerebral haemorrhaging [16-18], non-alcoholic steatohepatitis [19, 20] and inflammatory bowel disease [21]. We also demonstrated that cnm -positive S. mutans was associated with IgAN [22, 23].…”
Section: Introductionmentioning
confidence: 99%